2022
DOI: 10.1177/10775595211065761
|View full text |Cite
|
Sign up to set email alerts
|

Differential Response and the Reduction of Child Maltreatment and Foster Care Services Utilization in the U.S. From 2004 to 2017

Abstract: By 2014, the majority of U.S. states had implemented differential response (DR), a system policy that seeks to serve families of low-to moderate-risk for child maltreatment through family engagement, diversion from formal child protective services investigations, and service provision. However, the effects of DR programs on child welfare dynamics have yet to be evaluated nationally using causal methods. Using a quasi-experimental study design with data drawn from the National Child Abuse and Neglect Data Syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…Differential response is a CPS reform associated with child welfare caseload reductions. 31 Therefore, we adjusted for the presence of differential response programs and other sources of variation in child welfare system policies and practices between states in all analyses (eMethods in the Supplement ). In robustness checks we adjusted for state-funded cash assistance programs and the US opioid epidemic, which have been associated with child welfare caseload dynamics in past studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Differential response is a CPS reform associated with child welfare caseload reductions. 31 Therefore, we adjusted for the presence of differential response programs and other sources of variation in child welfare system policies and practices between states in all analyses (eMethods in the Supplement ). In robustness checks we adjusted for state-funded cash assistance programs and the US opioid epidemic, which have been associated with child welfare caseload dynamics in past studies.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, race and ethnicity and nativity have been associated with disparities in study outcomes in past research; therefore, we controlled for share of immigrants, Asian persons, non-Hispanic Black persons, persons of other races, and share of Hispanic persons of any race following census definitions. Differential response is a CPS reform associated with child welfare caseload reductions . Therefore, we adjusted for the presence of differential response programs and other sources of variation in child welfare system policies and practices between states in all analyses (eMethods in the Supplement).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, differential (or alternative) response (DR) programs provide the option of receiving services without having a formal CPS investigation response or without courts making a formal determination of substantiated abuse for families of low to moderate risk "screened into" child welfare. DR programs entail assessment of family needs and the provision of a continuum of services (including parenting, mental health, and substance abuse interventions; Johnson-Motoyama et al, 2023). Recent studies have found that the delivery of DR programs is associated with lower maltreatment substantiation and foster care placement (Johnson-Motoyama et al, 2023;Loman & Siegel, 2015).…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…DR programs entail assessment of family needs and the provision of a continuum of services (including parenting, mental health, and substance abuse interventions; Johnson-Motoyama et al, 2023). Recent studies have found that the delivery of DR programs is associated with lower maltreatment substantiation and foster care placement (Johnson-Motoyama et al, 2023;Loman & Siegel, 2015). However, in one study (Choi et al, 2021), children of color were less likely to be assigned to differential/alternative response programs than were White children, particularly if they were neglected.…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…More than half the states now apply this model, largely replacing the traditional investigation with an assessment of what a family needs, to most cases of neglect and less-severe physical abuse. The overall response of professionals and families suggests that this is a more constructive approach without increased recidivism and placements into foster care, compared with states without differential response …”
mentioning
confidence: 99%